Realismen og det unaturlige - Mäkelä, Maria (K&K - Kultur og Klasse, 2011)
REALISM AND THE UNCANNY. | Maria Mäkelä observes that the emergent trend of unnatural narratology has drawn most of its impetus from the strikingly transgressive, illogical or anti-mimetic elements of narrative construction, and that, consequently, texts that have established the firm ground of literary conventions – such as classical realist novels – have been playing the part of default narratives both in their representational design as well as in their experiential parameters. Mäkelä, howeverP– discussing in this essay salient examples from Dickens, Flaubert, and Tolstoy – finds that narratives under the heading of realism may have even more narratologically transgressive potential than the manifestly anti-experiential or anti-narrative extremes. Mäkelä’s text thus – inspired by some of Viktor Šklovsky’s seminal insights – aims at recovering the unnatural essence of the conventional in narrative fiction.